(NoPERY p(B. (Ni(B.(N~AJKOWSKOGO(B..s (NpUTEWODITELXs ((NmOSKWAs (NmUZYKAs, 1970)
(NpUTEWODITELX PO NAIBOLEE ZNA^ITELXNYM I REPERTUARNYMI OPERAM ~AJKOWSKOGO(B.(NsBORNIK OTKRYWAETSQ OBZORNOJ STATEJ OB OPERAH ~AJKOWSKOGO(B.s
Keywords: (NmONOGRAFIQs